REFERENCE VALUES OF DIFFERENT PARAMETERS OF VASCULAR STRUCTURE AND FUNCTION IN CAUCASIAN POPULATION WITHOUT CARDIOVASCULAR DISEASES. EVA STUDY. (June 2018) - Gomez-Sanchez, M.; Gómez-Sanchez, L.; Alonso-Domínguez, R.; Gonzalez-Sanchez, J.; Agudo-Conde, C.; Recio-Rodriguez, J.; Rodríguez-Martín, C.; Patino-Alonso, M.; Sanchez-Aguadero, N.; Castaño-Sánchez, C.; Maderuelo-Fernandez, J.; Rodriguez-Sanchez, E.; et al.
Abstract : Objective: To describe the mean values of different parameters of vascular structure and function, evolution with age and differences by gender in the general population without cardiovascular diseases. Design and method: Cross-sectional study in a general population cohort without cardiovascular diseases. Scope and Subjects: 360 subjects aged between 35 and 75 years old (51% female) were included, selected by random sampling stratified by age groups (35, 45, 55, 65 and 75 years) and gender using the base of Health Card of 4 urban Health Centers. Using ultrasonography, we measured the thickness of the intima media of the carotid artery (IMT). With the VaSera device, the Cardio Anckle Vascular Index (CAVI) and the pulse wave velocity ankle arm (aaPWV) were measured. With the Sphygmocor we measured the pulse wave velocity femoral carotid (cfPWV). Results: The mean values were: age 56.8 ± 14.9 years (males = 57.1 ± 14.4 and women = 56.6 ± 15.4, p = 0.730). GIM = 0.688 ± 0.114 mm (males = 0.708 ± 0.119 mm and females = 0.661 ± 0.108 mm, p = 0.020), CAVI = 8.19 ± 1.45 (males = 8.39 ± 1.44 and females = 8.02 ± 1.45, p = 0.015), aaPWV = 13.18 ± 2.81m/seg (males = 13.46 ± 2.52m/seg and women = 12.93 ± 3.02m/seg, p = 0.070) and cfPWV = 6.63 ± 2.04 m/seg (males = 6.97 ± 2.15 m/seg and females = 6.34 ± 1.91 m/seg, p = 0.004). For each year that the age increases, an increase of the IMT of 0.006 mm ((y = 0.364 mm +(0.006 mm * age)), in males 0.006 ((y = 0.365 mm+(0.006 mm * age)) and in women ((y = 0.363mm+(0.005 mm * age)) An increase in CAVI of 0.070 ((y = 4.212+(0.070 * age)), in males 0.071 ((y = 4.340+(0.071 * age)) and in women 0.069 ((y = 4.113+(0.069 * age)) An increase in aaPWV of 0.139 m/sec ((y = 5.276m/sec+(0.139m/sec * age)), in males 0.117 ((y = 6.785m/sec+(0.117 mm * age)) and in women 0.155 ((y = 4, 140m/sc+(0, 155m/sec * age)) and an increase in cfPWV of 0.088m/sec ((y = 1.655 m/sec+(0.088m/sec * age)), in males 1.458 ((y = 1.458m/sec+(0.097m/sec * age)) and in women 0.081 ((y = 1.784m/sec+(0.081m/sec * age)) Conclusions: All the parameters of structure and function analyzed, except for aaPWV, show average values and a greater annual increase in males comparing with females.